Paralogues From the Expanded Tlr11 Gene Family in Mudskipper (Boleophthalmus pectinirostris) Are Under Positive Selection and Respond Differently to LPS/Poly(I:C) Challenge - Qiu, Heng Tong; Fernandes, Jorge M. O.; Hong, Wan Shu; Wu, Hai Xu; Zhang, Yu Ting; Huang, Sheng; Liu, Dong Teng; Yu, Hui; Wang, Qiong; You, Xin Xin; Chen, Shi Xi (Frontiers in Immunology, 2019)
Toll-like receptors (TLRs) are major molecular pattern recognition receptors, which are essential for triggering a series of innate immune responses against invading pathogens by recognizing their evolutionary conserved molecular patterns. The mudskipper, Boleophthalmus pectinirostris is exceptional among fishes due to its amphibious lifestyle and adaptation to living on mudflats. The whole-genome sequencing of B. pectinirostris has revealed that this species possesses an expansion of Tlr11 family (12 Tlr11 family genes (one tlr21, 4 tlr22 and 7 tlr23)) that we focused on in the present study. The full-length cDNA sequences of the 12 tlrs in B. pectinirostris were cloned and their deduced amino acid sequences possessed a typical TLR domain arrangement. Likelihood tests of selection revealed that these 12 Tlr11 family genes are under diversifying selection. A total of 13 sites were found to be positively selected by more than one evolution model, of which 11 were located in the ligand-binding ectodomain. The observed non-synonymous substitutions may have functional implications in antigen and pathogen recognition specificity. These 12 tlrs were highly expressed in immune-related tissues, i.e. spleen and kidney. Tlr21 and tlr22b transcripts were significantly up-regulated by LPS, whereas tlr22a, tlr22d, tlr23b, tlr23e, tlr23g were significantly up-regulated by poly(I:C) in the spleen or/and kidney, which implies that the expanded Tlr11 family genes may play roles in protecting the fish from the invasion of gram-negative bacteria and double-stranded RNA viruses. The results from the present study suggested that the expansion of Tlr11 family genes in B. pectinirostris may recognize ligands from various pathogens found in the intertidal zone.